PEMANFAATAN LIMBAH SERBUK KAYU JATI (Tectona grandis) SEBAGAI MEDIA TUMBUH JAMUR TIRAM (Pleurotus ostreotus) - Muhammad Ilyas; Ira Taskirawati; Astuti Arif (Forestry Faculty of Universitas Hasanuddin, 2018)
Teak particle produced from sawmill industrial waste can be used as an alternative raw material for growing mushroom media. This study aims to get the productivity of oyster mushrooms that grow on teak particle growing media. The first treatment was carried out on teak particle before the particle was mixed with other ingredients, namely soaking teak particle using hot water (each for one, two and three hours) and cold water (each for five, seven and nine days). Soaking of teak particle influences the rate of fungal mycelium closure, the time of appearance of the mushroom fruit body, the fresh weight of mushrooms and the amount of mushroom harvest in each blog. On nine days of cold soaking, the blog is entirely covered by fungal mycelium on the 28th day, the mushroom fruit body appears on the 32nd day, the average fresh weight of mushrooms harvested 90 g and in one blog can collect mushrooms 2-3 times. The treatment of soaking wood particle in cold water for nine days showed better results compared to controls and other treatments.Key words: Pleurotus ostreotus, Tectona grandis, growing media